Approach to Individual Learning Curves: Call Center Colombia - Maza-Ávila, Francisco; Romero-Severiche, Ana Karina (EFIM Ediciones, 2020)
This article shows the results of the calculation of the individual learning curves for the workers of a call center in Colombia, in charge of offering mobile phone services. The analysis is made based on the experience and knowledge acquired for the development of their commercial activity and their relationship with the improvement in obtaining results, according to the sales objectives set. The empirical results obtained show that, as sales experience increases, the time spent on calls decreases.